Management and outcomes of hepatorenal syndrome at an urban academic medical center: a retrospective study. Issue 12 (December 2019) - Bashir, Muhammad H.; Iqbal, Sadat; Miller, Regina; Singh, Joie; Mubarak, Ghassan; Likhtshteyn, Michelle; Bigajer, Elliot; Gallagher, Bridget; Hurairah, Abu; Stefanov, Dimitre; McFarlane, Samy I.; Ferstenberg, Richard
Abstract : Objectives: This study is aimed to evaluate the management of acute kidney injury (AKI) in our inner city, American hospital. We intended to ascertain whether or not there is prompt recognition of AKI in cirrhosis according to International Club of Ascites and acute kidney injury network criteria as well how effective we are at distinguishing among different causes of AKI. We aimed to calculated the mortality of hepatorenal syndrome (HRS) in our hospital, and to evaluate the adequacy of the established treatment of AKI at each stage of its algorithm. Patients and methods: ICD diagnostic codes were used to identify patients with liver cirrhosis and acute renal failure. A total of 725 patients met the search criteria. We excluded the patients without clinical or imaging evidence of ascites, heart failure, on hemodialysis, baseline creatinine more than 1.5 mg/dl and patients who died within 48 h of developing acute renal failure. 291 patients met the inclusion criteria. All statistical analyses were performed using SPSS version 23.0 software with a two-sided significance level set at P value less than 0.05. Results: Mean age was 55.7 ± 0.61 and baseline serum creatinine was 0.94 ± 0.14. 66.5% of patients were African American, 27.3%, Hispanic, and 4.3% White. The average rise in creatinine from baseline was 1.36 ± 0.08 mg/dl. 27.2% of patients met the diagnostic criteria of HRS. 92.3% of patients with HRS received intravenous fluids and 75.4% received intravenous albumin within 48 h of acute creatinine rise. The in-hospital mortality rate was 14.1, 23.3, and 41.5% for patients with pre-renal azotemia, ARF, and HRS, respectively ( P < 0.01). Conclusion: This study demonstrates that with present tools, there is significantly higher mortality in HRS despite guideline-based treatment. Biomarkers for early diagnosis of HRS are necessary to avoid delays in initiation of HRS treatment while establishing the diagnosis. As well, worldwide standardization of the treatment of HRS will be important if the outcome is to be improved.